BIOLOGICAL ASSETS IN FINANCIAL STATEMENTS: CHALLENGES AND APPLICATIONS OF IAS 41 IN SERBIA - Kljajić, Maja; Jovanović, Mina; Kilibarda, Nataša; Mizdraković, Vule (The European Journal of Applied Economics, 2025)
Agricultural activities, due to several specific characteristics, are regulated by a separate standard - International Accounting Standard 41 - Agriculture, which makes a clear difference between biological assets and agricultural products. The purpose of this paper is to consider the representation of biological assets in the financial reporting of public companies in the territory of the Republic of Serbia. In addition, content analysis of audit reports of sampled companies has been performed in order to determine the compliance of financial reporting related to biological assets and regulatory framework. The research was conducted on two samples, out of which the first one consisted of 582 public companies from the Belgrade Stock Exchange during 2017, and the other one covered content analysis of audit reports of 397 public companies from 2018. The results of the research show that in the sector of agriculture, forestry and fisheries, the most common item is the value of biological assets, where 17 public companies disclosed the value of biological assets according to IAS 41. The analysis of auditor reports revealed that, in general, sampled companies complied with IAS 41 and other regulatory framework when reporting on biological assets.
Keywords: agricultural sector, fair value, IFRS, IAS, financial reporting.